Odpowiedzi

Najlepsza Odpowiedź!
2010-04-01T15:53:44+02:00

Sn = n*(n -2)
a1 = S1 = 1*(1-2) = 1*(-1) = -1
a1 +a2 = S2 = 2*(2 -2) = 2*0 = 0
-1 + a2 = 0 ---> a2 = 1
r = a2 - a1 = 1 - (-1) = 1 +1 = 2
Odp. a1 = -1 oraz r = 2
===============================
II sposób:
Sn-1 = (n-1)([(n-1) -2] = (n-1) *[n-3] = n² -4n +3
an = Sn - Sn-1 = n*(n-2) -(n² -4n +3) = n²-2n -n² +4n -3 = 2n -3
an+1 = 2*(n+1) - 3 = 2n +2 - 3 = 2n - 1
r = an+1 - an = 2n -1 -(2n -3) = 2n -1 -2n +3 = 3-1 = 2
a1 =2*1 -3 = 2 - 3 = -1
Odp. a1 = - 1 oraz r = 2
17 3 17